Evaluating the Hydrogen Chemisorption and Physisorption Energies for Nitrogen-Containing Single-Walled Carbon Nanotubes with Different Chiralities: A Density Functional Theory Study - Rozas-Soto, R; Contreras-Fuentes, M; Alvarez-Guenchuman, J; Cortes-Arriagada, D (Springer New York LLC, 2014)
The hydrogen adsorption energies for nitrogen-containing carbon nanotubes (N-CNTs) and for bare carbon nanotubes were calculated using the density functional theory methods at the B3LYP/6-31-G(d) level, including dispersion force corrections. The N-CNTs were finite saturated and non-saturated single-walled carbon nanotubes that contained one or more pyrimidine units, the relative positions of which defined the different configurations of the nanotube. The chemisorption of atomic hydrogen to a full exocyclic monolayer of zigzag, armchair, and chiral N-CNTs was studied as a function of the structural parameters. Zigzag N-CNTs of any configuration, with a larger number of nitrogen atoms, a small diameter and a small length, are more reactive compared to chiral and armchair N-CNTs. The presence of nitrogen in the carbon nanotubes enhances their reactivity to chemisorb atomic hydrogen, showing exothermic energy values. In contrast, the physisorption of molecular hydrogen was endothermic for most of the studied saturated N-CNTs, even when including corrections for van der Waals interactions. The endothermicity was greatest for zigzag nanotubes, then decreased for chiral nanotubes and decreased again for armchair nanotubes. In general, the endothermicity decreased for longer nanotubes, which have larger diameters, and a small number of nitrogen atoms. The results of this study suggest that, with saturated bare carbon nanotubes, saturated, and unsaturated N-CNTs could potentially have a higher capacity as hydrogen-storage media than the corresponding unsaturated carbon nanotubes. © 2013 Springer Science+Business Media New York.